Prevalence, distribution, and associated risk factors of molar incisor hypomineralisation among children in Kuantan Malaysia - Ardini, Yunita Dewi; Harun, Nor Asilah; Mohd Azni, Nur Diyana; Ismail, Nurul Naquiah (2014)

(untitled)
Objectives: The aim of this research was to determine the prevalence, distribution, and associations of molar incisor hypomineralization (MIH) with perinatal complications (PC), childhood illness (CI), and prolonged antibiotic consumption (PAC) among children attending the Polyclinic, Kulliyyah of Dentistry, IIUM, from February 2013 until December 2013. Materials and methods: A matched-pair case control study on children of 7 to 14 years of age was conducted. MIH was determined based on criteria from EAPD seminar, Athens 2003 (Weerheijm et al., 2003). Inter-examiner reliability was tested with Kappa statistic (0.80). This research was approved by the IIUM Research Ethic Committee (IREC). Results: Out of 201 patients, 25 were detected having MIH. The prevalence of MIH was 12.4% within the 11 month period. Among those 25 patients, 52.0% were boys and 48.0% were girls. Locations of MIH were found in maxilla (57%) and mandible (43%). There was no statistically significant association between MIH and arches (p=0.282) and gender (p=1.000). Chi-square goodness-of-fit test indicated that the three sites were not equally probable (p=0.000). Binomial test further showed that the probability of occurrence of MIH at the tip of canine (2.9%) was significantly lower (p=0.000) compared to the occlusal site of first permanent molar (FPM) (54.2%) and the cervical of incisors (42.9%). Analysis of risk factors indicated significant association between MIH with CI (p=0.000). No significant associations were found between MIH with PC (p=0.187) and PAC (p=0.489). Conclusion: MIH was not related to any particular arches and gender. It was also less likely to occur at the tip of canine. MIH was associated with CI but not with PC and PAC. Early diagnosis and prevention can minimize significant dental complications, reduce the risk of caries and provide a better clinical management for the patients.